Fall webworm, Hyphantria cunea (Drury) (Insecta: Lepidoptera: Arctiidae: Arctiinae) - Andrei Sourakov; Thomson Paris (EDIS)
This 9-page illustrated fact sheet describes this pest whose larvae form large tents in the foliage of many ornamental trees and shrubs, and also agronomic crops — synonymy, distribution, description and life cycle, hosts, economic importance, and management. Includes references. Written by Andrei Sourakov and Thomson Paris. Published by the UF Department of Entomology and Nematology as part of the Featured Creatures collection, December 2010.